Influence of the phosphate glass melt on the corrosion of functional particles occurring during the preparation of glass-ceramics. Issue 10 (July 2018) - Ojha, N.; Laihinen, T.; Salminen, T.; Lastusaari, M.; Petit, L.
Abstract: We report our findings on the impact of the glass composition on the corrosion of microparticles occurring during the preparation of glass-ceramics using the direct doping method. Microparticles (MPs) with the composition Sr4 Al14 O25 :Eu 2+, Dy 3+ with blue-green persistent luminescence were chosen as the changes in their spectroscopic properties can be related to the MPs' corrosion. The MPs were added in phosphate-based glasses with different compositions. When using the same doping parameters, the glass system with the composition 90NaPO3 -10Na2 O (mol%) was found to be the least corrosive on the MPs whereas the glass system with the composition 90NaPO3 -10NaF (mol%) is the most corrosive on the MPs probably due to their different viscosity at 575 °C, the temperature at which the MPs are added in the glass melts.